2006
DOI: 10.1186/1742-6413-3-16
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology of bone tumours--the experience from the National Orthopaedic and Lagos University Teaching Hospitals, Lagos, Nigeria

Abstract: BackgroundDue to difficulty in confirming clinical suspicions of malignancy in patients presenting with bone tumours, the cost of surgical biopsies where hospital charges are borne almost entirely by patients, competition with bone setters and healing homes with high rate of loss to follow up; we set out to find if sufficient material could be obtained to arrive at reliable tissue diagnosis in patients with clinical and radiological evidence of bone tumours in our hospitals.MethodsAfter initial clinical and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 4 publications
0
8
1
Order By: Relevance
“…Accuracy of FNAC to diagnose true benign and malignant neoplastic lesion was found to be 84%. sensitivity and positive predictive value found to be 80% and 86.9% respectively which are (10) more than the study done by Ramana S.V et al , but lesser (9) than other studies like Obiageli E Nnodu O E et al and Jain (11) Vet al .…”
Section: Discussionmentioning
confidence: 60%
“…Accuracy of FNAC to diagnose true benign and malignant neoplastic lesion was found to be 84%. sensitivity and positive predictive value found to be 80% and 86.9% respectively which are (10) more than the study done by Ramana S.V et al , but lesser (9) than other studies like Obiageli E Nnodu O E et al and Jain (11) Vet al .…”
Section: Discussionmentioning
confidence: 60%
“…The cytological exam permitted the diagnosis of a malignant mesenchymal tumor highly suggestive of osteosarcoma within a short period of time and even before the biopsy result. In addition, the imprint method permitted the collection of cells of excellent quality for analysis and more refined visualization of cellular aspects than in biopsy material, considering that the cells suffer modifications during the process of decalcification of the material [ 11 - 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that have examined pre-biopsy imaging demonstrated a poor positive predictive value for malignancy (50% – 75%). 17,18,19,20,21,22,23 On the contrary, other studies have shown higher sensitivities and specificities when including MRI and computer-aided detection. 24,25,26,27 Given the paucity of literature on this topic locally, this study was implemented to test a radiologist’s interpretation of plain radiographs against a histopathological diagnosis.…”
Section: Introductionmentioning
confidence: 99%